The functions of autophagy at the tumour‐immune interface. Issue 5 (18th February 2021) - Luo, Xiaobo; Qiu, Yan; Dinesh, Palani; Gong, Wang; Jiang, Lu; Feng, Xiaodong; Li, Jing; Jiang, Yuchen; Lei, Yu L.; Chen, Qianming
Abstract: Autophagy is frequently induced in the hypoxic tumour microenvironment. Accumulating evidence reveals important functions of autophagy at the tumour‐immune interface. Herein, we propose an update on the roles of autophagy in modulating tumour immunity. Autophagy promotes adaptive resistance of established tumours to the cytotoxic effects of natural killer cells (NKs), macrophages and effector T cells. Increased autophagic flux in tumours dampen their immunogenicity and inhibits the expansion of cytotoxic T lymphocytes (CTLs) by suppressing the activation of STING type I interferon signalling (IFN‐I) innate immune sensing pathway. Autophagy in suppressive tumour‐infiltrating immune subsets maintains their survival through metabolic remodelling. On the other hand, autophagy is involved in the antigen processing and presentation process, which is essential for anti‐tumour immune responses. Genetic deletion of autophagy induces spontaneous tumours in some models. Thus, the role of autophagy is context‐dependent. In summary, our review has revealed the dichotomous roles of autophagy in modulating tumour immunity. Broad targeting of autophagy may not yield maximal benefits. The characterization of specific genes regulating tumour immunogenicity and innovation in targeted delivery of autophagy inhibitors into certain tumours are among the most urgent tasks to sensitize cold cancers to immunotherapy.